2005
DOI: 10.1074/jbc.m414217200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Heparanase-inhibiting Activity of Heparin through Selective Desulfation, Graded N-Acetylation, and Glycol Splitting

Abstract: Heparanase is an endo-␤-glucuronidase that cleaves heparan sulfate (HS) chains of heparan sulfate proteoglycans on cell surfaces and in the extracellular matrix (ECM). Heparanase, overexpressed by most cancer cells, facilitates extravasation of blood-borne tumor cells and causes release of growth factors sequestered by HS chains, thus accelerating tumor growth and metastasis. Inhibition of heparanase with HS mimics is a promising target for a novel strategy in cancer therapy. In this study, in vitro inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 204 publications
(155 citation statements)
references
References 59 publications
(127 reference statements)
5
147
0
Order By: Relevance
“…Since these drugs can also inhibit heparanase activity [46,47], it is possible that their ameliorating effect on proteinuria is due to inhibition of heparanase. A study by Levidiotis et al [48] showed that inhibition of heparanase with the specific heparanase inhibitor PI-88 reduced proteinuria in passive Heymann nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Since these drugs can also inhibit heparanase activity [46,47], it is possible that their ameliorating effect on proteinuria is due to inhibition of heparanase. A study by Levidiotis et al [48] showed that inhibition of heparanase with the specific heparanase inhibitor PI-88 reduced proteinuria in passive Heymann nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…depolymerization, and preserves both the pattern and degree of sulfation [98,99]. Periodate can selectively oxidize adjacent carbons bearing unsubstituted hydroxyl and /or amino groups [100], leading, in heparins, to the splitting of C(2)-C(3) bonds of un-sulfated uronic acids including the glucuronic acid, within the ATBR, essential for high anticoagulant activity [101].…”
Section: Glycol-split Heparins (Gs-heparins)mentioning
confidence: 99%
“…The methyl groups also mimics the anomeric carbon of the next unit in a polysaccharide chain. In the framework of our whole project, fully protected 1,6-anhydro containing trisaccharides will be used as synthetic intermediates and, in passing, Several studies have been carried out to understand the structure-activity relationship of heparin for heparanase inhibition, including variation in the degree of 2-O-sulfation, 6-O-sulfation, N-sulfation, N-acetylation, glycol-split uronic acid [13,14]. These studies led to conclude that O-2-sulfation of IdoA and O-6 sulfation of GlcN were not essential for effective inhibition, and that one N-sulfate group per disaccharide units was in interaction with the enzyme [7].…”
Section: Chemistrymentioning
confidence: 99%